Polyethylene glycol (PEG-400) as a medium for novel and efficient synthesis of 2-phenyl-2,3-dihydroquinazolin-4(1H)-one derivatives - Yerram, Parthasaradhi; Chowrasia, Rakhi; Seeka, Suresh; Tangenda, Savitha Jyostna (European Journal of Chemistry, 2013)
A novel, efficient synthesis of 2-phenyl-2, 3-dihydroquinazolin-4(1H)-one derivatives is reported for the ﬁrst time in PEG-400 by the reaction of various aldehydes, anthranilamide under catalyst-free conditions and the formation of product good to excellent yields. PEG-400 can be recovered and reused without any significant loss of activity.